Peningkatan Kualitas Pelayanan di BNI Syariah Dengan Pendekatan Customer Relationship Management (CRM) - Chuzaimah Batubara; Nailan Ni’mah Sinaga (Madani: Jurnal Ilmiah Multidisiplin, 2023)
With the aim of increasing business value for customers, Customer Relationship Management System (CRM) focuses on the theory of business-customer relationship management. You can also think of this as an integrated computer system, which monitors the activity of the company before and after the sale. This study examines the growth and application of CRM in the Indonesian banking sector. The task of this research is to provide a deeper understanding of the application of CRM in BRI sharia banks by examining various available research sources and literature. We conducted research on BRI Shariah using online media to determine whether it uses CRM to attract loyal customers. The research was conducted by the author by examining various publications and journals on the application of CRM in the BRI Sharia bank. In the near future, the results of this analysis will be used to improve the understanding of the application of Sharia CRM in Indonesia.